2023
DOI: 10.1039/d2nr06077a
|View full text |Cite
|
Sign up to set email alerts
|

In situ quantitative single-molecule study of site-specific photocatalytic activity and dynamics on ultrathin g-C3N4 nanosheets

Abstract: Single-molecule fluorescence microscopy was applied to quantify photocatalytic activities and dynamics at individual structural features of g-C3N4 nanosheets at nanometer resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Previously, it has been shown that the resorufin molecule takes advantage of its planarity, whereby p-p stacking amplified the interaction between BP and resorufin. 10 The adsorption energies of AR across all three CNS surfaces are still much higher than resorufin, indicating the preference to bind the reactant more than the product. The differences of the adsorption energies of the two species on the BP, edge and wrinkle are 0.27, 0.16 and 0.06 eV, which explains the trend of k 3 in Table 1.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, it has been shown that the resorufin molecule takes advantage of its planarity, whereby p-p stacking amplified the interaction between BP and resorufin. 10 The adsorption energies of AR across all three CNS surfaces are still much higher than resorufin, indicating the preference to bind the reactant more than the product. The differences of the adsorption energies of the two species on the BP, edge and wrinkle are 0.27, 0.16 and 0.06 eV, which explains the trend of k 3 in Table 1.…”
mentioning
confidence: 94%
“…Therefore, in this work, we intend to apply SMF imaging to fill the gaps and address the photocatalytic heterogeneity issues on g-C 3 N 4 . Compared with our previous work studying the site-specific properties of photoreduction reactions on 2D materials, 10 this work successfully quantified the rate constants of photo-oxidation kinetics at individual structural features of g-C 3 N 4 . It was found that wrinkles possess the highest turnover rate and rate constants of conversion and direct dissociation, followed by edges and basal planes (BPs).…”
mentioning
confidence: 99%
“…3 Since the groundbreaking report by Fujishima and Honda in 1972, 4 photocatalytic hydrogen evolution from water has been considered a promising method for using solar energy to obtain clean and sustainable energy. 5 A large number of semiconductors, such as TiO 2 , 6 g-C 3 N 4 , 7 and transition metal sulfides, 8,9 have been widely developed as photocatalysts for hydrogen evolution. However, the H 2 -production activities are unsatisfactory, and unfavorable thermodynamics, slow kinetics, dissolved oxygen, reverse reactions, and side reactions make the overall photocatalytic cracking of water very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The achievement of SMF technology was acknowledged by the Nobel Prize for Chemistry in 2014. [ 9 ] In recent years, SMF techniques have been utilized to analyze site‐specific reactivities and dynamics on nanomaterials (e.g., single nanoparticles, [ 11 ] 1D nanowires, [ 12 ] 2D nanosheets, [ 13 ] etc.) to address the catalytic heterogeneity issues.…”
Section: Introductionmentioning
confidence: 99%